Potential Cosmeceutical Applications of Extract of Polygonum odoratum Lour - เด่นชัย รัฐศาสตร์; แซ่อู้ อรุณรัตน์; ตรีนุชกร มัชฌิมา (Koch Cha Sarn Journal of Science, 2021)
Peaw or Polygonum odoratum Lour. belongs to family of Polygonaceae. Every parts of plant have an unique aroma. In the past, folk medicine brings the whole plants with a spicy flavor use for drive gastric air Relieve bloating and flatulence. Nowadays, its extract of Polygonum odoratum Lour have been studies regarding its pharmacological activities, but It’s not utilized. There is also no report to support which part of extract is suitable for product development. The aim of this study was to investigate the biological activities of Polygonum odoratum Lour extract from whole plant. Extracts of Polygonum odoratum Lour were prepared by soaked of ethanol. Antioxidant activities were determined by using 2,2-diphenyl-1-picrylhydrazyl. Dopachrome method was used for determination of anti-tyrosinase activity. The results showed exhibited antioxidant activities with IC50 values of 26.644±1.141 µg/mL. The Extract from hole plant exhibited anti-tyrosinase activities with IC50 values of 117.94±19.08 µg/mL, Antioxidant effects and anti-tyrosinase activities of the extract of Polygonum odoratum Lour showed lower activities than that of ascorbic acid and Kojic acid respective. Therefore, extract of Polygonum odoratum Lour from whole plant have a potential to develop as the cosmeceutical products for skin whitening and antioxidant applications.